OPTIMALISASI ROUTING MENGGUNAKAN SATU AUTONOMOUS SYSTEM NUMBER (ASN) BORDER GATEWAY PROTOCOL (BGP) - Muhammad Arif Zaky Zamany; Hendra Supendar; Sulistianto Sutrisno Wanda (JEIS: Jurnal Elektro dan Informatika Swadharma, 2022)
Network routing that still uses two as numbers on the border gateway protocol, which allows the second as number to be a backup, which can be said to be ineffective. Moreover, the admin cannot know the backhoul network interference before monitoring a mass disturbance, so routing is switched manually. A Border Gateway Protocol is a path vector routing protocol that coordinates the routing of packets through multiple administrative domains by computing routes between every IP address the packet passes. Certain routers, called BGP speakers, are assigned to run the protocol. BGP speakers across different Autonomous Systems (AS) are interconnected in order to exchange routing information. BGP supports a feature called multihoming, which means connecting to multiple ISPs from different routers or points in the network. by using BGP one As Number, routing can choose the best or shortest path.